Preparartion of using information communication and technology in teaching and learning among technical the teacher of technical school - Yahaya, Azizi; Chia, Swee Yee (2006)

(untitled)
The aim of this study was to identify the preparation of using Information Communication and Technology (ICT) in teaching and learning from aspects of knowledge, skills, attitude and confidence among the technical teachers of technique schools in Johore, Malacca and Negeri Sembilan. A total of 92 teachers from nine technical schools in three states were randomly selecting (cluster over cluster method) in this study. The findings showed that the preparation of Technical teachers’ knowledge, skills, attitude and confidence in using Information Communication and Technology in teaching and learning was at high level. The findings also showed that the level of preparation have significant difference with frequency in using computer and computer ownership.